Lisbon as a home port for cruise tourism - Baeta, Daniel Filipe da Silva (2017)
Over the last decade, cruise tourism has become a significant source of revenue for many regions like the Mediterranean. Passengers who (dis)embark on a cruise typically spend two to three nights in the (dis)embarking city, therefore spending more money than tourists on transit, who typically only spend about eight hours in town. However, most cruise tourists who arrive in Lisbon are on transit. This work project aims to discuss ways to increase the number of cruises that begin/end their journeys in Lisbon, considering factors such as incentives and promotion, as well as the recent investment on a new cruise terminal.